The effect of differentiated instruction on the development of reading comprehension skills in EFL beginner students - Hidalgo-Camacho, Cynthia Soledad; Hernández-Chérrez, Elsa de los Ãngeles; Galora-Moya, Nelly Patricia (Dominio de las Ciencias, 2019)
The purpose of this study was to investigate the effect of Differentiated Instruction (DI) on the development of reading skills in English as Foreign Language (EFL) beginner undergraduate students, as well as to evaluate their perceptions of the effectiveness of DI on reading lessons. The sample was made up of 69 Ecuadorian EFL learners, divided in two groups: 36 students who were part of the experimental group, and 33 from the control group. The research instruments were a diagnostic reading test, a Pre-test and a Post-test on reading comprehension skills, and an exit survey about students’ opinions about the use of DI in the EFL classroom. The research results showed that before intervention, in the diagnostic reading test, both groups had a low percentage of reading understanding, while the post-test results were significantly higher. Additionally, the students acknowledged the effectiveness of DI as a tool for teachers to meet the learners’ individual needs and interests, as well as a way to generate opportunities to develop reading abilities at a literal level. Students agreed that DI motivated them to read in English and boosted their self-confidence to do it aloud. Therefore, it can be said that DI is as an effective and motivating methodology that can be implemented in the EFL classroom for the development of reading comprehension skills.